Rancang Bangun Piranti Lunak Pengelola Parameter Akuisisi Data Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Data acquisition is an important part of a series of activities in a wind tunnel test and determine the validity of aerodynamic characteristics information of the test object. One of the factors which affect the success of the data acquisition process is the control of the data acquisition parameters prior to the execution of the wind tunnel test. A large number of data acquisition parameters, and the configuration complexities of the data acquisition parameters, which are still managed manually, urged the development of a software which is expected to facilitate the management of these parameters in a way that is friendly to use and integratable into the existing data acquisition system. Engineering of data acquisition parameters management software was then carried out through the analysis, design and implementation stages in an iterated manner, starting with a simple prototype toward the establisment of operational product.